Measurement of Relative Efficiency Using Data Envelopment Analysis (DEA) Method to Improve Efficiency in Perum Pegadaian Syariah - Aryani, Enny; Iriani; Rusindiyanto; Endang Pudji W; M. Frizky Feri Setiawan; Fadilla Umeida Putri (Tekmapro, 2025)
The development of the Islamic financial industry which includes banking, insurance and pawnshops is basically a very long historical process. Perum Pegadaian Syariah, as one of the state-owned enterprises, is faced with the challenge of competing and improving efficiency in the growing Islamic financial industry. This study aims to measure the operational efficiency of Islamic Pawnshops in East Java Province using the Data Envelopment Analysis (DEA) method. This study identifies the relative efficiency of each Pawnshop unit from several branches of Pegadaian Syariah, including Joko Tole, Babakan, Sidokare, Mayjend Sungkono, and Blauran. The results showed that four branches were efficient with a relative efficiency value of 1, while Sidokare branch showed inefficiency with a value of 0.908. Improvement recommendations for Sidokare branch include reducing service time, operating costs, and increasing the number of customers and collateral. This research is expected to guide Perum Pegadaian Syariah in contributing to improving efficiency and competitiveness in an increasingly competitive market.